Synthesis, Characterization and Antimicrobial Screening of Mixed 5-(4-Chlorophenyl)-6-Ethyl- 2,4-Pyrimidinediamine-Aspirin Metal Drug Complexes - Bamigboye, Mercy Oluwaseyi; Lawal, Misitura; Ginikachukwu , Grace (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
A new series of complexes of 5-(4-chlorophenyl)-6-ethyl- 2,4-pyrimidinediamine-aspirin metal drug has been synthesized as potential antimalarial and analgesic activity which yielded excellent results. The synthesized complexes have been evaluated using some analytical techniques such as conductivity measurements, elemental analysis and spectroscopic analysis such as atomic absorption spectroscopy and FT-IR. The result of the conductivity measurement showed the compounds to be non-electrolyte and suggests a tetrahedral geometry. The ligands used are bidentate in nature. In pyrimethamine complexes, coordination occurred through the nitrogen of the N-H and C=N groups as seen in the results obtained from the FT-IR analysis. In aspirin, the coordination occurred through the oxygen of the C=O and O-H group. The novel complexes have been screened and investigated against some isolated organisms namely: Escherichia coli, Bacillus megaterium, Proteus vulgarius, Pseudomonas aeruginosa, Euterobacter aerogenes, Staphylococcus aureus, Bacillus substillis and Serratia marcesceus. Higher activity was observed due to ability to decrease the population of the bacterial species. This research work was carried out with the aim of improving the effectiveness and antibacterial activity of the parent ligands